Hepatotoxic and hemolytic effects of acute exposure of rats to artesunate overdose (International Journal of Medicine and Medical Sciences, 2020)
Hepatotoxic and hemolytic effects of artesunate overdose were examined in rats. Forty (40) rats were grouped randomly into four designated as A, B, C, and D. and were given oral administration of artesunate as follows: 0 mg/kg (control), 1 mg/kg (Under-dose), 2 mg/kg (Normal dose) and 4 mg/kg (Overdose) respectively. The administration was continued for 5 days. Hepatotoxicity was monitored in the rats as a function of changes in serum levels of aspartate transaminase (AST), alanine transaminase (ALT), alkaline phosphatase (ALP), total serum albumin and malondiadehyde (MDA) level. The hemolytic effect of this drug was monitored by changes in the packed cell volume (PCV), total bilirubin, conjugated bilirubin and malondiadehyde (MDA) levels of erythrocyte. For group D (overdose group) subjects when compared with the control (group A), there was significant (p